Analisis Minat Belajar Matematika Siswa Kelas V Sd Negeri 40 Matang Segantar Melalui Pendekatan Pendidikan Matematika Realistik Indonesia (Pmri) - Zainal (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aims to analyze the mathematics learning interests of fifth-grade students at SD Negeri 40 Matang Segantar using the Indonesian Realistic Mathematics Education (PMRI) approach. The study used a descriptive approach with a two-cycle classroom action design. The research subjects were 30 students. Data were obtained through observation sheets of learning interests covering activeness, cooperation, and courage, then analyzed using percentages and descriptive interpretation. The PMRI principles were applied through the use of realistic problems, concrete media, group discussions, opportunities to explain strategies, and reflection. The results showed an increase in the good category in the activeness indicator from 45% in cycle I to 85% in cycle II. Cooperation increased from 55% to 90%, while courage increased from 60% to 90%. These findings indicate that mathematics learning that starts from real experiences, manipulation of concrete objects, and communication between students can strengthen learning engagement. PMRI provides space for students to see mathematics as an activity close to life, not just a formula to be memorized. This study recommends that elementary school teachers use PMRI systematically in materials on arithmetic operations and spatial figures.